Impacto de la contaminación de la minería informal en el cerro el toro - huamachuco - Corcuera Horna, César Augusto (2016)
The aim of the research was to determine the impact of pollution from its activities in the informal artisanal mining in the Cerro el Toro and its surrounding areas such as: in the Town Low (CPM) Center Shiracmaca, Caserío El Toro, Coigobamba, District of Huamachuco; Province of Sanchez Carrion, La Libertad Region. The study was conducted by analyzing secondary sources such as technical reports from the Ministry of Energy and Mines, Ministry of Health, Public Prosecutor and other public and private entities; site visits to mining areas of influence and the area where the activity takes place. The research analysis indicates that in the Cerro el Toro mining concessions there are 7 Environmental Impact Study (EIA) approved, while a no EIA has. It was determined that there are on average 02 - 05 per work Pozas (adits) and 06 workers for each pool, in total 2268 workers. Presence of cyanide ponds built by hand; Remove mineral treatment product thrown on the side of the pools of cyanide, where there are no retaining walls and drainage system. The results of the impact of pollution on the activity of informal mining in the Cerro el Toro presented a highly critical impact regarding environmental parameters: soil quality, water quality, air quality, population health, diversity of flora and fauna. Acceptable impact: population growth, traditional activity and lifestyle. It is concluded that the impacts generated by informal mining in the Cerro El Toro are: (a) negative to life, environment and population; (b) the environment is in grave danger because the work is done in areas adjacent to homes, affecting growing areas, undermining the flora and fauna; (c) there are pools of cyanide and abandoned workings and environmental liabilities that are deteriorating soils and crop areas. The positive impact we can mention the increase of labor and labor as a means of livelihood for the people and the dynamism of trade; conducting a cost analysis: profit between positive and negative impact is concluded that the negative impact is greater because these are irreversible damage to health and the environment.